SOCIAL-CULTURAL AND DIGITAL-BASED COMMUNITY EMPOWERMENT TOWARDS SUSTAINABLE TOURISM IN THE SITU GEDE LAKE AREA - Saragi, Charles Parnauli; Mulyana, Ade; Cahyadi, Septian; Utami, Nisa Rahmaniyah; Verdian, Zidan Zulfan; Muljadi, Maharani Putrinya (LPPM Univ. Ibn Khaldun Bogor, 2025)
Situ Gede Tourism Village, a natural lake surrounded by forests and open areas, is a major attraction for tourists seeking to enjoy nature and local culture. Situ Gede is also known for its recreational activities, such as boating, lake walks, and nature photography. Although Situ Gede Tourism Village has great potential, several issues need to be addressed and addressed to enhance its competitiveness as a tourism destination. These include: Limited Management, Lack of Digital Promotion and Accessibility, and Lack of Digital Promotion and Accessibility. Therefore, several solutions are proposed, including Community Training and Empowerment in tourism areas such as local culture, local cuisine, and digitalization to manage and market the tourism village. Development of a digital platform for technology-based tourism promotion, booking, and management. Sustainable Environmental Management through more organized conservation and waste management programs. The conclusion of this activity, overall, fosters synergy between socio-cultural aspects, the digital economy, and environmental sustainability as an important foundation for realizing an inclusive, innovative, and community-based sustainable tourism model in the Situ Gede Lake area.